Optimasi Kualitas Sealing terhadap Produk Bad Seal pada Mesin Filling Auto Cup Sealer - Margianto , Yosy; Finahari, Nurida; Soebiyakto, Gatot (Widyagama University of Malang, 2024)
The rapid growth has an impact on consumer demand for quality products, high quality and safe for consumption. In the production of cup packaged beverages after a series of product manufacturing processes are completed until they are released to the next process, bad seal leaking products are still found (poor sealing). Bad seal leaks are caused by a poor sealing process so that the product is not evenly sealed and results in packaging leakage considering that it can damage the quality and quality of the product. This research uses a real experimental method (True Experimental Research) using tensile testing with a Tensile Strenght Test tool. After conducting experiments on the appropriate settings to reduce the occurrence of bad seals in the filling machine sealing process, a parameter of 7 bar is set for each heater block, at the baket rotation speed setting after analyzing the parameter data carried out by the filling operator and QC line and conducting experiments, the appropriate parameter setting is obtained to reduce the occurrence of bad seal products, namely speed 5 (20 rpm) with a sealing process of 0.16 seconds, with the temperature that has been analyzed, a temperature of 200 ℃ is obtained as the appropriate standard temperature.